STRATEGI PEMBELAJARAN AKTIF PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR NEGERI BANTUIL 1 MARABAHAN - M.Fazrian Noor Irfan; Saifuddin Saifuddin (ADDABANA: Jurnal Pendidikan Agama Islam, 2019)
This study discusses the active learning strategies of Islamic education in the Bantuil State Elementary School 1 Marabahan. The problem formulation in this study is how the active learning strategy of Islamic education in the Bantuil State Elementary School 1 and the supporting aspects of active learning strategy of Islamic education in the state elementary school Bantuil 1. This type of research is field research using qualitative descriptive methods. The subject in this study was the principal, the teacher of Islamic education, the administration and students at the Bantuil State Elementary School 1. While the object in this research is an active learning strategy of Islamic Education and its visitor aspects. The techniques used in data collection are observations, interviews, and documentation with the principal's data sources, Islamic religious education teachers, administration and students at the Bantuil State Elementary School 1. The results of the study showed that the active learning strategy of Islamic education in the Bantuil State Elementary School 1 was well carried out, this can be seen from the preparation by the teacher before the study, sorting the content presentation Lessons, the use of learning methods and the evaluation of learning outcomes. While the supporting aspects found in the form of a competent teacher aspect, students who are familiar with Islamic educational lesson materials, and the environment that pays attention to the student's future. Keywords: Learning strategy, active learning, Islamic religious education.